144k views
5 votes
Select True or False. The expression 3x − 4(2x − 5) is equivalent to the expression 20 − 5x.

2 Answers

3 votes

Answer:

TRUE

Explanation:

3x - 4 ( 2x-5)

-4 x 2x = -8x

-4 x -5 = 20

3x - 8x +20

= 20 - 5x

User Shubham Pachori
by
5.9k points
4 votes

Answer:

True

Explanation:

Expand -4(2x - 5)

Apply the distributive law

-4 * 2x - (-4) * 5

Apply minus plus rules

-4 * 2x + 4 * 5

Simplify

-8x + 20

3x - 8x + 20 = 20 - 5x

Add similar elements

-5x + 20 = 20 - 5x

Subract 20 from both sides

-5x + 20 - 20 = 20 - 5x - 20

Simplify

-5x = -5x

Add 5x to both sides

-5x + 5x = -5x + 5x

Simplify Once more

0 = 0

So the answer is true.

User NikhilWanpal
by
6.3k points